Quinomycin A reduces cyst progression in polycystic kidney disease. Issue 5 (7th April 2021) - Radadiya, Priyanka S.; Thornton, Mackenzie M.; Daniel, Emily A.; Idowu, Jessica Y.; Wang, Wei; Magenheimer, Brenda; Subramaniam, Dharmalingam; Tran, Pamela V.; Calvet, James P.; Wallace, Darren P.; Sharma, Madhulika
Abstract: Polycystic kidney disease (PKD) is a genetic disorder characterized by aberrant renal epithelial cell proliferation and formation and progressive growth of numerous fluid‐filled cysts within the kidneys. Previously, we showed that there is elevated Notch signaling compared to normal renal epithelial cells and that Notch signaling contributes to the proliferation of cystic cells. Quinomycin A, a bis‐intercalator peptide, has previously been shown to target the Notch signaling pathway and inhibit tumor growth in cancer. Here, we show that Quinomycin A decreased cell proliferation and cyst growth of human ADPKD cyst epithelial cells cultured within a 3D collagen gel. Treatment with Quinomycin A reduced kidney weight to body weight ratio and decreased renal cystic area and fibrosis in Pkd1 RC/RC ; Pkd2 +/− mice, an orthologous PKD mouse model. This was accompanied by reduced expression of Notch pathway proteins, RBPjk and HeyL and cell proliferation in kidneys of PKD mice. Quinomycin A treatments also normalized cilia length of cyst epithelial cells derived from the collecting ducts. This is the first study to demonstrate that Quinomycin A effectively inhibits PKD progression and suggests that Quinomycin A has potential therapeutic value for PKD patients.